Ever since Darwin : reflections in natural history - Gould, Stephen Jay (Norton Paperback, 1979)
Stephen Jay Grould is one of the brillant of our younger biologists, gifted, among other things, whit the ability to write. These essays, on a fascinating variety of topics in natural history, are original, informative, enlightening, and stimulating.